2016
DOI: 10.1016/j.envsoft.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support Tool for energy-efficient, sustainable and integrated urban stormwater management

Abstract: Highlights• The E²STORMED Decision Support Tool for stormwater management is presented.• It complements financial analyses with energy and environmental criteria.• It provides robust decision criteria for informed stormwater management.• This tool encourages a more sustainable urban water management.• The tool is very useful to promote SuDS between local and regional decision makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 13 publications
0
20
0
2
Order By: Relevance
“…Regarding SUDS selection, the definition of the best system or set of structures have comprised two main approaches: (a) performance evaluation through models to determine runoff volume reduction [30,31], and (b) multicriteria analysis considering qualitative and/or quantitative explanatory variables mainly at local scale and microscale [32,33]. The use of models can involve a high computational cost and requires detailed information that is not always available, particularly for a preliminary evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding SUDS selection, the definition of the best system or set of structures have comprised two main approaches: (a) performance evaluation through models to determine runoff volume reduction [30,31], and (b) multicriteria analysis considering qualitative and/or quantitative explanatory variables mainly at local scale and microscale [32,33]. The use of models can involve a high computational cost and requires detailed information that is not always available, particularly for a preliminary evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Green roofs are one specific type of SUDS consisting of areas of living vegetation; they are installed on the top of buildings, which promotes the reduction of surface water runoff quantity and pollution, and also provides ecosystem services such as aesthetic benefits, ecological-added value, and an enhancement of building performance [4,5]. Interest in green roofs has increased in recent years, as many more benefits have been reported beyond the hydrological ones: energy savings, thermal benefits, air pollution improvement, carbon sequestration, and psychological benefits [6][7][8]. Kuronuma et al [9] demonstrated that green roofs contribute actively to carbon sequestration and energy savings, thus enhancing global warming mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…The opinion of the subjects who considered the construction and maintenance costs to be higher than those of the grey infrastructures is probably influenced by their lack of familiarity with these interventions, which have not yet been carried out systematically. To support the cost-benefits evaluation of these infrastructures, decision support systems exist that allow for the comparison of different drainage scenarios, conventional or with the use of WrGIs/SuDSs, on construction and maintenance costs, energy consumption, greenhouse gas emissions, and the provision of ecosystem services (i.e., E 2 STORMED; [52]).…”
Section: Attitude Towards Wrgis/sudssmentioning
confidence: 99%